Do Leading Macroeconomic Factors Impact on Optimal Portfolio Return in Indonesia? - Bayu Adi Nugroho; Edhi Juwono; Inung Wijayanti (Binus Business Review, 2018)
There were two objectives in this research. Those were to construct an optimal portfolio and to analyze the impact of inflation, Bank of Indonesia (BI rate), and Rupiah to US Dollars exchange rate to the optimal portfolio return in Indonesia. The constant correlation portfolio model and ordinary least square regression method were implemented. This research used the stocks from the consistently selected stocks in the Bisnis-27 Index from 2012 to 2016. Microsoft Excel 2010 was used to construct an optimal portfolio. Meanwhile, to compute the regression and statistical analysis, SPSS version 20 was utilized. The obtained results show that only the stocks from PT Telekomunikasi Indonesia, PT Kalbe Farma, PT Charoen Pokphand Indonesia, PT Bank Rakyat Indonesia, PT Bank Central Asia, and PT Bank Negara Indonesia are included in the optimal portfolio. In addition, from the three leading macroeconomic indicators, only exchange rate change (Rupiah to US Dollars rate of change) impacts the return of the constant correlation model portfolio in Bisnis-27 Index significantly and negatively.